Spinal Intradural Extramedullary Capillary Hemangioma: MR Imaging Findings - Yoon Choi, Bo; Chang, Kee-Hyun; Choe, Gheeyoung; Hee Han, Moon; Park, Sun-Won; Kyu Yu, In; Hee Park, Yang; Jip Kim, Hyun (American Journal of Neuroradiology, 2001)
Summary: Spinal intradural extramedullary capillary hemangiomas are extremely rare. We present the MR imaging and histologic findings in three patients with this abnormality. The three patients were men who had symptoms of either myelopathy (n = 2) or radiculopathy (n = 1). The tumors were well demarcated, 1.5–2.0 cm in diameter, and were located at the posterior or posterolateral portion of the thecal sac (one at the L1 level and the other two at the midthoracic level). On MR images, the tumor showed isointensity relative to the spinal cord on T1-weighted images, hyperintensity on T2-weighted images, and strong homogeneous enhancement on contrast-enhanced T1-weighted images in all three patients. In two patients, the dural tail sign was observed. Capillary hemangioma should be included in the differential diagnosis of a spinal intradural extramedullary tumor.